Neuroanatomical correlates of language impairment in non-fluent variant of primary progressive aphasia - Diliara R. Akhmadullina; Rodion N. Konovalov; Yulia A. Shpilyukova; Kseniya V. Nevzorova; Ekaterina Yu. Fedotova; Sergey N. Illarioshkin (Frontiers in Human Neuroscience)
IntroductionNon-fluent variant of primary progressive aphasia (nfvPPA) is a neurodegenerative disorder with a predominantly speech and language impairment. Apraxia of speech and expressive agrammatisms along with decreased speech fluency and impaired grammar comprehension are the most typical disorder manifestations but with the course of the disease other language disturbances may also arise. Most studies have investigated these symptoms individually, and there is still no consensus on whether they have similar or different neuroanatomical foundations in nfvPPA. In addition, only few works have focused on the functional connectivity correlates. The aim of our study was to simultaneously investigate functional and structural brain-language associations in one group of nfvPPA.MethodsTwenty eight patients were enrolled and underwent brain MRI and language assessment. Apraxia of speech, expressive and receptive agrammatisms, repetition, naming and single word comprehension correlates were identified using voxel-based morphometry and resting-state functional MRI (ROI-to-ROI analysis).Results and discussionAmong the structural correlates, the most common were inferior frontal gyrus (was associated with fluency, both expressive and receptive agrammatisms) and supramarginal gyrus (apraxia of speech, receptive agrammatisms, naming and repetition). Apart from that, neuroanatomical foundations were different for each of the core nfvPPA language domains, including superior parietal lobule involvement in fluency, temporoparietal areas in receptive agrammatisms and supplemental motor area in apraxia of speech. Functional correlations were even more diverse. In general, connectivity decrease between temporoparietal structures was more typical for expressive and receptive agrammatisms, single word comprehension and naming, while apraxia of speech, fluency and repetition showed connectivity disruption mainly among the frontoparietal region and subcortical structures. Overall, extensive structural and functional changes are involved in the development of language and speech disturbances in nfvPPA with distinctive neuroanatomical foundations for each domain.